Aptitude for Interpreting. - Pöchhacker, Franz; Liu, Minhua (Amsterdam/Philadelphia : John Benjamins Publishing Company, 2014)
With increasing numbers of students wishing to become conference interpreters, but limited capacities in most university degree programs, accurate admission testing is an important means of predicting an applicant's chances of completing the program successfully. This article focuses on three aptitude tests for simultaneous interpretation: Pöchhacker's SynCloze test; Chabasse's cognitive shadowing test; and Timarová's personalized cloze test. The test battery was administered at the start of the 2009/2010 academic year to students beginning the two-year Master's program in conference interpret.
Discussion and conclusionsImplications for interpreter education; References; Domain-general cognitive abilities and simultaneous interpreting skill; Introduction; Method; Participants; Rating; Measurements; Cognitive Ability Measurements; Emotion-Cognition Interaction Measurements; Procedure; Results and discussion; Univariate analyses; Multivariate analyses; Discussion; General discussion and future directions; References; Testing aptitude for interpreting; 1. Introduction; 2. Methods; 2.1 Participants; 2.2 Scoring; 2.3 Outcome measures; 2.4 Statistical analysis; 3. Results.
Print version record.
3.1 Scores on all variables.
Includes bibliographical references and index.
eBooks on EBSCOhost
Keywords: Translating and interpreting -- Study and teaching; FOREIGN LANGUAGE STUDY -- Multi-Language Phrasebooks; LANGUAGE ARTS & DISCIPLINES -- Alphabets & Writing Systems; LANGUAGE ARTS & DISCIPLINES -- Grammar & Punctuation; LANGUAGE ARTS & DISCIPLINES -- Linguistics -- General; LANGUAGE ARTS & DISCIPLINES -- Readers; LANGUAGE ARTS & DISCIPLINES -- Spelling; Translating and interpreting -- Study and teaching; Electronic book